Organic Anion Transporting Polypeptides in the Hepatic Uptake of PBDE Congeners in Mice - Pacyniak, Erik (2011)
BDE47, BDE99 and BDE153 are the predominant polybrominated diphenyl ether (PBDE) congeners detected in humans and can induce drug metabolizing enzymes in the liver. We have previously demonstrated that several human liver organic anion transporting polypeptides (humans: OATPs; rodents: Oatps) can transport PBDE congeners. Mice are commonly used to study the toxicity of chemicals like the PBDE congeners. However, the mechanism of the hepatic PBDE uptake in mice is not known. Therefore, the purpose of the current study was to test the hypothesis that BDE47, BDE99, and BDE153 are substrates of mouse hepatic Oatps (Oatp1a1, Oatp1a4, Oatp1b2, and Oatp2b1). We used Human Embryonic Kidney 293 (HEK293) cells transiently expressing individual Oatps and quantified the uptake of BDE47, BDE99, and BDE153. Oatp1a4, Oatp1b2, and Oatp2b1 transported all three PBDE congeners, whereas Oatp1a1 did transport none. Kinetic studies demonstrated that Oatp1a4 and Oatp1b2 transported BDE47 with the greatest affinity, followed by BDE99 and BDE153. In contrast, Oatp2b1 transported all three PBDE congeners with similar affinities. The importance of hepatic Oatps for the liver accumulation of BDE47 was confirmed using Oatp1a4-, and Oatp1b2-null mice.